Optimalisasi Komunikasi Anak Speech Delay Melalui Strategi Penanganan dan Pembelajaran Bahasa - Ndiy, Asri Cicilia; Amseke, Fredericksen (Edudikara: Jurnal Pendidikan dan Pembelajaran, 2024)
Delay in speaking or speech delay is one of the problems experienced by children. The aim of the research is to determine the optimization of communication in speech delayed children through language handling and learning strategies for five year old children who experience delays in speaking. The subjects of this research were one parent and one child. The research method in this research is a descriptive qualitative research method. This research uses data collection techniques through interviews and documentation studies. The results of this research are the optimization of speech delay children's communication through language handling and learning strategies. The results of this research show that appropriate and effective language learning and handling strategies can help improve the communication skills of speech delayed children, thus facilitating optimal language development and improving the quality of interactions with the surrounding environment which can ultimately improve the quality of life of speech delayed children. The conclusion is that the importance of the family's role in helping children overcome speech delays cannot be denied. For this reason, parents have a very important role in providing support, stimulation and a supportive environment for children's language development.